Association of Common Carotid Artery Doppler‐Determined Dicrotic Notch Velocity With the Left Ventricular Ejection Fraction. (1st March 2015) - Polak, Joseph F.; Alessi-Chinetti, Jean M.; Patel, Ayan R.; Estes, James M.
Abstract : Objectives: The appearance of the dicrotic notch on blood pressure tracings is associated with impaired cardiac function. Common carotid artery waveforms have similar fiduciary markers, yet they have not been related to cardiac function. We studied associations of common carotid artery dicrotic notch velocities with the left ventricular ejection fraction (LVEF) determined by echocardiography. Methods: We conducted a retrospective study of 37 patients who had cardiac echocardiography and carotid Doppler evaluations within 1 day of each other. The LVEF was determined by the biplane modified Simpson rule. Doppler parameters were measured from tracings of the left common carotid artery 4 cm from the flow divider. Linear regression and stepwise multivariable linear regression models were used to evaluate any association between the LVEF and the following variables: age, sex, peak systolic velocity (PSV), end‐diastolic velocity (EDV), dicrotic notch velocity, rise time (EDV to PSV), resistive index, and cardiac cycle length. Results: The dicrotic notch velocity was the only variable associated with the LVEF ( P = .028) in a bivariate analyses. A backward selection stepwise multivariable equation predicting the LVEF had the dicrotic notch ( P = .001) and resistive index ( P = .01) as significant predictors, whereas the cardiac cycle length ( P = .08) and PSV ( P = .08) were borderline not significant. Model goodness of fit was R 2 = 0.37 ( P = .004). Conclusions: Dicrotic notch velocities measured from common carotid artery Doppler waveforms are associated with the LVEF and might offer some clinical value in selected cases.